A Preanalysis Plan to Replicate Sixty Economics Research Papers That Worked Half of the Time - Chang, Andrew C.; Li, Phillip (American Economic Review, 2017)
We attempted to replicate 67 macroeconomic papers using author-provided data and code files by following a preanalysis plan. Excluding 6 papers that used confidential data, we obtained data and code replication files for 29 of 35 papers (83 percent) that were required to provide such files as a condition of publication, compared to 11 of 26 papers (42 percent) that were not required to provide such files. Also excluding the 2 papers that used software we did not possess, we replicated 29 of 59 papers (49 percent) with assistance from the authors. We conclude with recommendations on improving replication of economics research.